2013
DOI: 10.1055/s-0032-1317847
|View full text |Cite
|
Sign up to set email alerts
|

New, Efficient Approach for the Ligand-Free Suzuki–Miyaura Reaction of 5-Iodo-2′-deoxyuridine in Water

Abstract: A series of 5-aryl-2′-deoxyuridines was prepared, using ligandless Suzuki-Miyaura cross-coupling reactions in neat water, starting from 5-iodo-2′-deoxyuridine as totally deprotected starting material. This ligand-free process gave good to high isolated yields within short reaction times and with low loadings of palladium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 34 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The authors also discovered that TPPTS was not even required when the reaction was conducted at 100 o C, and the loading of palladium catalyst may be reduced to 0.01 mol%, although with much longer reaction times (24 hours). 42 Using the same ligand, Ejlersen et al reported its application for an on-column modification of oligonucleotides containing 5-iodo uridine motif, which eliminated the need for a base additive and facilitates separation and purification. 43 In 2012, a simple approach of utilizing the Suzuki-Miyaura reaction for the synthesis of 5-aryl uracils was reported by Fresneau et al, 44 who screened several phosphine ligands and found that the commonly used triphenylphosphine (PPh3) was optimal to achieve good yields of 5-substituted-2'-deoxyuridine products 15 in a completely water-soluble medium (Figure 8A).…”
Section: Synlett Account / Synpactsmentioning
confidence: 99%
“…The authors also discovered that TPPTS was not even required when the reaction was conducted at 100 o C, and the loading of palladium catalyst may be reduced to 0.01 mol%, although with much longer reaction times (24 hours). 42 Using the same ligand, Ejlersen et al reported its application for an on-column modification of oligonucleotides containing 5-iodo uridine motif, which eliminated the need for a base additive and facilitates separation and purification. 43 In 2012, a simple approach of utilizing the Suzuki-Miyaura reaction for the synthesis of 5-aryl uracils was reported by Fresneau et al, 44 who screened several phosphine ligands and found that the commonly used triphenylphosphine (PPh3) was optimal to achieve good yields of 5-substituted-2'-deoxyuridine products 15 in a completely water-soluble medium (Figure 8A).…”
Section: Synlett Account / Synpactsmentioning
confidence: 99%
“…Good yields can be achieved using water as the only solvent [70,75,76]. In the case of the more reactive 5-IdU, the TPPTS ligand is not required [77]. Good yields could be achieved with electron-rich arylboronic acids, but much lower yields were obtained with electron-deficient boronic acids.…”
Section: Aqueous-phase Cross-coupling Of Nucleosides Nucleotidesmentioning
confidence: 99%